Stereocontrolled Cascade Cyclisation of Campholenic Enol Ether Derivatives: En Route to Vetiver‐Scented Spiroxides. Issue 8 (23rd February 2018) - Ondet, Pierrick; Filippi, Jean‐Jacques; Lemière, Gilles; Duñach, Elisabet
Abstract : The Lewis superacid‐catalysed cascade cyclisation of enol ethers derived from campholenal resulted in an elegant reaction leading to new elaborated spirocyclic ethers. Under identical conditions, the reaction proceeded by two distinct mechanisms, depending on the relative configuration of the starting substrate. Hence, either a tandem cyclisation process gave access to tetracyclic spirodiethers, while another process involving a less common reaction sequence (cyclisation/1, 4‐hydride shift) led to complex tricyclic spiroalcohols and/or spiroketones. Investigations on synthetic intermediates by enantioselective gas chromatography permitted to assess the high stereospecificity of the process. Collectively, these expedite syntheses gave access to unprecedented spiroxides which displayed, in some instances, strong vetiver‐like olfactory notes. While campholenic derivatives have long been used in the industrial production of fragrant sandalwood substitutes, these new derivatives provide potential synthetic alternatives to the esteemed natural ingredient vetiver. Abstract : The cascade cyclisation of dienol ethers derived from optically active campholenal gives access to a wide range of spirocyclic compounds. Several instances in the series revealed olfactory notes strongly reminiscent of vetiver. This work constitutes the first example of fragrant campholenic derivatives with vetiver‐like properties.